Urban rat races: spatial population genomics of brown rats (Rattus norvegicus) compared across multiple cities. Issue 1880 (6th June 2018) - Combs, Matthew; Byers, Kaylee A.; Ghersi, Bruno M.; Blum, Michael J.; Caccone, Adalgisa; Costa, Federico; Himsworth, Chelsea G.; Richardson, Jonathan L.; Munshi-South, Jason
Abstract : Urbanization often substantially influences animal movement and gene flow. However, few studies to date have examined gene flow of the same species across multiple cities. In this study, we examine brown rats ( Rattus norvegicus ) to test hypotheses about the repeatability of neutral evolution across four cities: Salvador, Brazil; New Orleans, USA; Vancouver, Canada; and New York City, USA. At least 150 rats were sampled from each city and genotyped for a minimum of 15 000 genome-wide single nucleotide polymorphisms. Levels of genome-wide diversity were similar across cities, but varied across neighbourhoods within cities. All four populations exhibited high spatial autocorrelation at the shortest distance classes (less than 500 m) owing to limited dispersal. Coancestry and evolutionary clustering analyses identified genetic discontinuities within each city that coincided with a resource desert in New York City, major waterways in New Orleans, and roads in Salvador and Vancouver. Such replicated studies are crucial to assessing the generality of predictions from urban evolution, and have practical applications for pest management and public health. Future studies should include a range of global cities in different biomes, incorporate multiple species, and examine the impact of specific characteristics of the built environment and human socioeconomics on gene flow.